If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -6 + y = -7 + 3y Reorder the terms: -6 + -3y + y = -7 + 3y Combine like terms: -3y + y = -2y -6 + -2y = -7 + 3y Solving -6 + -2y = -7 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -6 + -2y + -3y = -7 + 3y + -3y Combine like terms: -2y + -3y = -5y -6 + -5y = -7 + 3y + -3y Combine like terms: 3y + -3y = 0 -6 + -5y = -7 + 0 -6 + -5y = -7 Add '6' to each side of the equation. -6 + 6 + -5y = -7 + 6 Combine like terms: -6 + 6 = 0 0 + -5y = -7 + 6 -5y = -7 + 6 Combine like terms: -7 + 6 = -1 -5y = -1 Divide each side by '-5'. y = 0.2 Simplifying y = 0.2
| 10x-7=7x+5 | | 4(x-3)-x=3(x-4) | | 5(x+2)=5x-2 | | 6+7x=-36 | | 8b+5=12+7b | | -4x-1=-7 | | 4(y-4)=8 | | y=3x+4 | | 5x+2=2(x+6) | | 9-30x=-42-27x | | -5x+10=45 | | 5+6=126 | | z+11.2=-6.5 | | 56=112z | | 12x+8-4=11x-3 | | 48=6m | | 1.5x^2-24x-24=0 | | -10=k-11 | | 7=x-9 | | -6+y=-11 | | 15x-5=10x+35 | | 13x-2y=70 | | -6(1-2x)-12=0 | | y=-5x-7 | | 4x+-10=-4x+22 | | 4(2z-4)=-4(z-2) | | 7(3-y)=-3y+5 | | 4x+93=-3x+9 | | 6c=4(c+5) | | -5(6n+2)=20 | | 15.7x-2.7x=-26 | | 6a+3=8a-21 |